2003
DOI: 10.1063/1.1586461
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced cation migration in Cu oxide films by in situ scanning tunneling microscopy

Abstract: Published by the AIP Publishing Articles you may be interested inOxygen adsorption-induced nanostructures and island formation on Cu{100}: Bridging the gap between the formation of surface confined oxygen chemisorption layer and oxide formation Deposition of gold nanofeatures on silicon samples by field-induced deposition using a scanning tunneling microscope J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This stabilization is perhaps correlated to the dissolution of V (for OER, will be discussed in the following section) and a rearrangement (e.g., redox reaction, dissolution, electromigration) of the catalyst surface. [ 21 ] They are maintaining stable within 2 h.…”
Section: Resultsmentioning
confidence: 99%
“…This stabilization is perhaps correlated to the dissolution of V (for OER, will be discussed in the following section) and a rearrangement (e.g., redox reaction, dissolution, electromigration) of the catalyst surface. [ 21 ] They are maintaining stable within 2 h.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to nanowires of oxides, electric field-assisted growth of metal and semiconductor nanostructures have been reported for other materials, e.g., copper, [48] silicon, [49] or zinc. [50]…”
Section: Effect Of An External Electric Field On Oxide Nanowire Growth During Thermal Oxidationmentioning
confidence: 99%
“…19 Electromigration, which takes place inside the metal wire, would contribute to the formation of the oxide layer with micro and nanostructures by favoring diffusion processes towards the surface. Results on the synthesis of Cu nanowires under a STM tip 24 and on CuO nanowires 25 by heating Cu foils at 400 C on a hotplate indicated that the process is favored by the application of an external electric eld, which promotes the diffusion/electromigration of Cu ions. 25 In the case of Mo, a thermal assisted electromigration process would enhance the out diffusion of Mo ions in the metal wire leading to the rapid growth of MoO 3 plates.…”
Section: Structures Formed On the Mo Wirementioning
confidence: 99%